Projections of Potential Flood Regime Changes in California - Dettinger, Michael D. (2009)
Floods have been a recurring theme in California’s climatology, hydrology, and politics throughout its history. Today, California's aging water supply and flood protection infrastructures are challenged by major floods and increased standards for urban flood protection. With warming in the twenty-first century, some changes in California’s flood regimes seem likely: Higher snowlines may well increase the frequency of flooding; occasional larger than historical flood magnitudes are likely to follow—especially from the higher southern parts of the Sierra Nevada; potentials for floods may be exacerbated by wetter winter soils in high-altitude catchments; and opportunities for estuarine and coastal flooding may increase as sea-level rise and flood frequencies converge. Other changes are more difficult to project, and simulation models are used here to weigh competing influences that might either increase or diminish future floods. Both the Variable Infiltration Capacity (VIC) and Bay-Delta Watershed Model (BDWM) hydrologic models responded to downscaled climate-change projections with increases in flood frequencies and magnitudes, but neither yielded large changes in that regard, especially in the northern parts of the state. Future characteristics of major storms, in particular pineapple express or atmospheric river storms, by global climate models indicated changes mostly at the extremes: Years with many atmospheric river storms become more frequent in most climate models analyzed here, but the average number of such storms per year did not change much. Likewise, although the average intensity of storms was not projected to increase much in most climate models, occasional much-larger-than-historical-range storm intensities were simulated